Polymorphism in chalcogenides of alkalineearth metals - Drozdov, V.А.; Pozhivatenko, V.V.; Drozdov, М.А.; Kovalchuk, V.V.; Moiseev, L.M.; Moiseeva, V.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Calculations of structural phase transitions В1 - В2 under pressure in chalcogenides of alkaline-earth metals were carried out on the basis of approach of the local density functional theory, where as a fitting used was the constructive amendments of the potential by means of the electronic density received in a self-coordinated calculation using the approximation of the local density.